Challenges experienced by family caregivers of patients in palliative care: an integrative literature review - Gomes, Elizandra Regina dos Santos; Lima, Angélica de Godoy Torres; de Meneses, Uberlândia Islândia Barbosa Dantas; de Aquino, Jael Maria; Silva, Darine Marie Rodrigues da; Correia, Erika Soares; Costa, Diogo Timóteo; Silva, Maria Thereza da Motta e; Santos, Ana Paula Rodrigues dos; Bezerra, Ana Beatriz França (Seven Editora, 2023)
Objective: To reveal the challenges experienced by family caregivers of patients in palliative care. Method: This is an integrative literature review study carried out in four databases: BDENF, IBCS, LILACS, MEDLINE. On these bases, two descriptors identified in the DECS were crossed, such as: palliative care and caregivers. To search for the articles, a combination of descriptors was performed with the Boolean operator "AND". Results: The final sample comprised 13 articles published in national journals, with several challenges identified, among which stood out: the imposition to exercise the role of caregiver without personal choice; a change in the routine of life; the complete abdication of one’s life due to the care of the loved one; living with psychosomatic symptoms; illness from depression; emotional exhaustion due to living with worsening symptoms and certainty of death; lack of knowledge to perform daily tasks. Conclusions: It become necessary to know the challenges experienced in the daily dynamics of care and to plan actions that contribute to alleviate the suffering and physical and psychological illness of caregivers. This fact requires training, personal investment and detachment from professionals to be with the other, in an ethical and empathetic way, in facing death. DOI: https://doi.org/10.56238/colleinternhealthscienv1-051